Construction of concern: resumption and specification in textual articulation - Wiedemer, Marcos Luiz (2025)
Based on the theoretical framework of Usage-Based Constructional Grammar (Goldberg, 2006; Diessel, 2023), in this paper we focus on investigating the grammatical construction represented by the scheme [[X(constructor referente) [Preposition(em) + Anaphoric mostrative (o)]NO Relative Pronoun (que) [respeito/se refere/tange/concerne] Y[SN(specifier refernt]], which we call the "concern construction". To this end, we analysed the microconstructions "no que diz respeito a", "no que se refere a", "no que tange a" and "no que concerne a" in Brazilian Portuguese. The data is taken from the Now Sample of the Portuguese Corpus, covering the period from 2012 to 2019. The general results show that the construction of concern occurs in the resumption of a given referent between the two textual portions, called ‘specified all-part resumption’, which involves the resumption of one referent (X) by means of another (Y) to specify it. This retaking can take two forms: (i) all-part specified retaking; and (ii) all-selection specified retaking. The retaken and specified referent can range from a lexeme to a discourse topic, occurring mainly in preceding paragraphs. The specifying relation plays a role in coercing the referent Y, indicating a discursive object.